Rudimentary halteres of some flightless female Phoridae (Diptera) reassessed, and some taxonomic implications - Disney, R. Henry L. (Zootaxa, 2005)
The supposed rudimentary halteres of the flightless females of the Neotropical Ecituncula halterata Borgmeier and genus Pulicimyia Borgmeier are reinterpreted as wing rudiments. Consequently E. halterata is transferred to the genus Ecitophora Schmitz, creating a junior synonym of E. breviptera Disney. Pulicimyia is synonymised with Puliciphora Dahl and the resulting Puliciphora modesta (Borgmeier) comb. nov. makes a homonym with the Afrotropical P. modesta (Disney), which is therefore renamed P. etiamodesta nom. nov. The replacement name P. edaphomyia nom. nov. is proposed for the Afrotropical P. nigriventris (Borgmeier), as the name is preoccupied by an older synonym of a widely distributed Old World species. The Neotropical Homalophora epichaeta Borgmeier is transferred to Puliciphora, with the consequent synonymy of P. mexicanae Disney with this species. The Neotropical P. sobria Borgmeier is reported from the Nearctic Region, and P. cavatica Disney is synonymised with it. P. jacquemarti sp. nov. is described from Puerto Rico. A revised key to Nearctic Puliciphora females is provided.